First Brazilian Case Report of Unrelated Patients with Identical ISG15 Mutation - Napoleao, Sarah Maria da Silva; Salgado, Ranieri Coelho; Ferreira, Janaira Fernandes Severo; de Barros Dorna, Mayra; de Moura, Thais Costa Lima; França, Tábata Takahashi; Barreiros, Lucila Akune; Gomes, Lillian Nunes; Condino-Neto, Antonio (Journal of clinical immunology, 2025)
Background ISG15 deficiency is a mixed syndrome of Mendelian susceptibility to mycobacterial infections (MSMD), a rare inherited condition characterized primarily by recurrent infections from low-virulence mycobacteria and monogenic type I interferonopathy. Objective To characterize the laboratory and molecular features of two patients from different families affected by the same ISG15 variant. Methods We began with clinical characterization and investigation, assessed IL-12/IFN-γ production, performed genetic characterization through WES and Sanger sequencing, conducted an in silico molecular analysis of the genetic ISG15 variant’s protein impact, and utilized RNAseq for transcriptome analysis to understand pathway impacts on ISG15 -deficient subjects from unrelated families. Results A mutation in the ISG15 gene was identified, affecting two patients treated in different hospitals and cities in Brazil (Fortaleza and Sao Paulo), who are also members of unrelated families. Both patients showed low IFN-γ production when stimulated with BCG or BCG + IL-12. ISG15 deficiency presented with two distinct clinical phenotypes: infectious and neurological. It was identified that both patients are homozygous for the variant (c.83 T > A). Furthermore, it was observed that the mutant protein p.L28Q results in an unstable protein with increased flexibility (ΔΔG: -2.400 kcal/mol). Transcriptome analysis revealed 1321 differentially expressed genes, with significant upregulation in interferon pathways, showing higher expression in patients compared to controls. Conclusion This study describes the first reported cases in Brazil of two unrelated patients with the same ISG15 mutation c.83 T > A, exhibiting infectious features such as mycobacterial infections and systemic candidiasis, neurological findings, and skin lesions, without adverse reactions to the BCG vaccine. Clinical Implications Reporting ISG15 gene mutations in Brazilian patients enhances understanding of genetic susceptibilities, guiding effective diagnostics and treatment. Identifying high-risk individuals aids clinical practices, genetic counseling, and influences public health policies. Capsule Summary We have identified the first case in Brazil of the same ISG15 variant c.83 T > A that was identified in two unrelated patients with distinct clinical phenotypes, infectious and neurological.